Optimalisasi Penerimaan Pendapatan Asli Daerah (PAD) Kabupaten Minahasa - Pongoh, Stefany Putri Gabriella; Dilapanga, Abdul Rahman; Mantiri, Jeane (Tumoutou Social Science Journal, 2024)
This study aims todetermine how to optimize local revenue in Minahasa Regency. The method used in this research is a qualitative method with data collection techniques through interviews, documentation and observation. The research focuses on the target groundwater tax object, the targets and realization of groundwater tax revenue and the factors that affect groundwater tax revenue. The research location is at the regional revenue agency office of Minahasa Regency. The result of research on the optimization of local revenue in Minahasa Regency show that: 1) By targeting tax objects, it is easier for local governments to collect taxes, but not all groundwater tax objects have been recorded as taxpayers. 2) The revenue targets in 2022 was not achieved as set. 3) Revenue realization is different from the revenue target or does not match. 4)There is difference between usage and payment/does not match, the awareness of the people who are groundwater taxpayers is still lacking or disobedient so it is necessary to increase socialization activities to all taxpayers so that taxpayers can clearly understand the importance of paying taxes.